Keanekaragaman Bulu Babi (Echinoidea) Di Perairan Distrik Maladum Mes Kota Sorong - Oktovianus Hosio; Abdul H. A. Toha; Vera Sabariah (Program Pascasarjana Universitas Papua, 2023)
The aim of this study was to determine and describe the species diversity of sea urchins in the Maladum District Waters of Sorong City. The study took place in Pantai Tampa Garam, Pantai Alinda and Pantai Tanjung Batu of Sorong waters. The method used was purposive sampling with a line transect sampling technique measuring 1 x 1 meter in size. The research was found 5 species of sea urchin namely Echinometra mathaei, E. oblonga, Diadema setosum, Astropyga radiata, and Tripneustes gratilla. Tanjung Batu had higher sea urchin species richness and diversity and a greater relative abundance (2.17 ind/cm2) of E. mathaei than Pantai Alinda (2 ind/cm2). The Shannon diversity index (H') of sea urchin ranges from H'= 0.48–0.89. The highest value of H’ is in Pantai Tampa Garam which have three species. The lower diversity values in Pantai Tanjung Batu which have two species. Simpson’s index of dominance (D) ranged from 0.48 to 0.69 and dominated by sea urchin E. mathaei in Tanjung Batu. While Pielou’s species evenness index (J) ranged from 0.69 to 0.88.